Berkhotbah Untuk Transformasi: Kunci Kontekstualisasi Pesan Khotbah dalam Realitas Kehidupan Modern - Silvanoes Semuel Kaligis (Sekolah Tinggi Teologia Kerusso Indonesia, 2022)
This research elucidates the importance of sermon contextualization, audience understanding, andser mon goal clarification in preaching in modern churches. Through a comprehensive literature review and in-depth analysis of various literary sources, this study identifies the principles and best practices in sermon contextualization to make it relevant to congregants' daily lives. Additionally, it highlights the crucial role of audience understanding in determining the effectiveness of sermons and the urgency of setting clear goals to ensure the conveyed message has a positive impact. The practical implications of these findings emphasize the need for developing skills in understanding the audience and the courage to articulate messages that prompt positive change. Furthermore, recommendations for future research include further investigation into effective sermon contextuali-zation methods and their influence on spiritual transformation in society.